Resonansi Bragg Pada Aliran Air Akibat Dinding Sinusoidal Di Sekitar Muara Sungai - Viska Noviantri (ComTech: Computer, Mathematics and Engineering Applications, 2010)
Basically, the water wave (wave) that passes through uneven base will have a solution to the wave transmission and reflection. It has been found also that the sinusoidal basis with certain conditions can cause the Bragg resonance. This paper will show that the wave propagation through the wall of river water can also cause sinusoidal Bragg resonance. Bragg resonance will occur if the sinusoidal wall of the wave number twice the number of incoming waves. Both analytically and numerically, the river wall with amplitude sinusoidal small amplitude can be reduced significantly due to the Bragg resonance. More specifically, the situation would be different if we consider the river mouth in the form of a hard wall of the dam. The existence of the hard wall of the dam at the mouth of the river it can cause the amplitude of the waves crashing against the transmission of large dams increased many-fold.